Knowledge management in hospitality and tourism / Ricarda B. Bouncken, Sungsoo Pyo editors - Bouncken, Ricarda B.
"Knowledge management in hospitality and tourism has been co-published simultaneously as Journal of quality assurance in hospitality & tourism, volume 3, numbers 3/4 2002."